THE EFFECT OF IMPLEMENTING A DIRECT LEARNING MODEL WITH GEOGEBRA SOFTWARE TOWARD STUDENTS’ MATHEMATIC CONCEPT COMPREHENSION ABILITY DERIVED FROM THEIR SELF-EFFICACY - Suhartini; Hayatun Nufus (Jurnal Prinsip Pendidikan Matematika, 2021)
This research aimed to know the effect of implementing a direct learning model with Geogebra on students' mathematic concept comprehension ability derived from their self-efficacy. It was an experimental research with a factorial experimental design. All the eleventh-grade students of pharmacy major at vocational High school of Ikasari Pekanbaru in the academic Year of 2019-2020 were the population of this research. The samples of this research were the eleventh-grade students of Pharmacy 6 as the Experimental group and the students of Pharmacy 2 as the Control group. The Cluster Random Sampling technique was used in this research. The data collection techniques were a test, questionnaire, observation, and documentation. The data collection instruments were the teacher and student observation sheets, mathematic concept comprehension ability pretest and posttest: self-efficacy questionnaire, and documentation. The technique of analyzing the data was two-way ANOVA. Based on the data analysis, it could be concluded that 1) there was a difference in mathematic concept comprehension ability between students taught by using Direct learning model with Geogebra software and those who were taught by using Conventional learning, 2) there was a difference in mathematic concept comprehension ability among students having high, medium, and low self-efficacy, 3) there was no interaction between learning model and self-efficacy toward student mathematic concept comprehension ability. So it could be concluded that implementing the Direct learning model with Geogebra software was affected by students' mathematic concept comprehension ability derived from their self-efficacy.